Hybrid sterility, Haldane's rule and speciation in Heliconius cydno and H. melpomene (2002)
Most genetic studies of Haldane’s rule, in which hybrid sterility or inviability affects the heterogametic sex preferentially, have focused on Drosophila. It therefore remains unclear to what extent the conclusions of that work apply more generally, particularly in female-heterogametic taxa such as birds and Lepidoptera. Here we present a genetic analysis of Haldane’s rule in Heliconius butterflies. Female F1 hybrids between Heliconius melpomene and H. cydno are completely sterile, while males have normal to mildly reduced fertility. In backcrosses of male F1 hybrids, female offspring range from completely sterile to fully fertile. Linkage analysis using the Z-linked triose-phosphate isomerase locus demonstrates a “large X” (Z) effect on sterility. Expression of female sterility varies among crosses in this and a previous study of Heliconius. Sterility may result from the production of normal but infertile eggs, production of small infertile eggs, or from a complete failure to develop ovarioles, which suggests multiple routes to the evolution of hybrid sterility in these Heliconius species. These results conform to the expectations of the “dominance” rather than “faster male” theories of Haldane’s rule and suggest that relatively few loci are responsible. The two species are broadly sympatric and hybridize in the wild, so that female hybrid sterility forms one of several strong but incomplete barriers to gene flow in nature. The effect of female sterility is comparable to that of selection against non-mimetic hybrids, while mate choice forms a much stronger barrier to gene transfer.